Automatic Additive Manufacturing Product Generation Through Computer Aided Process Planning Using 3D/4D/5D Printing - Ilias, Izzah Nadhilah (Universiti Sains Malaysia, 2022)
Additive manufacturing (AM), often referred to as rapid prototyping or 3D printing in the scientific literature, has evolved as a popular manufacturing technology since the 1980s. The utilisation of AM technology or 3D Printing has continues to grow throughout the years as it is one of the leading emerging technologies of Industry 4.0. However, most of the process are done manually where the users need to convert the 3D model to machine language, which is G-code in order to print the model. Therefore, an integrated CAD/CAM system are used to automated the printing process by creating an algorithm that able to decide the type of printing process (3D, 4D or 5D printing) suitable with the model and convert it to STL file automatically. Then, the algorithm will be tested whether it can be extended up to 5D printing by using three different types of models with a different printing process. The results of this project are focused on the creation of macro result, generation of G-code result and fabrication of product. This project has successfully created an algorithm that can identify the type of printing process and convert CAD file to STL file automatically. The algorithm has also been tested and able to produce a complete additive manufacturing product by using an integrated CAD/CAM system with a 3D printer. A further experiment should be done to test functionality of the algorithm and identify the accuracy of the algorithm.